THE EFFECT OF PEER TEACHING METHOD ASSISTED BY E-MODULE MEDIA ON STUDENTS' CONCEPT UNDERSTANDING AND SCIENTIFIC ATTITUDE - Risky Indah Yuliasari; Haslinda Yasti Agustin (EDUCATUM: Scientific Journal of Education, 2024)
The difficulty of students in understanding the concept of classification of living things is complicated because it has many branches of classification. Educators who tend to provide material using the lecture method cause the learning process to be less varied. This will have an impact on students' low understanding and scientific attitude in learning so that it will affect their activity in class. The method used is quasi experimental with nonequivalent control group design. Data collection methods are tests and observations. The observation sheet was used to obtain data on students' scientific attitudes. Tests were used to obtain data on students' concept understanding. Data analysis used prerequisite tests and hypothesis tests. The prerequisite test is normality and homogeneity test while the hypothesis test uses independent sample T-test, Manova test and Effect size. Aiming to analyze the effect of peer teaching method assisted by e-module media on students' concept understanding and scientific attitude on the material of Classification of Living Things in class VII MTs PSM Tanen Rejotangan. The results of this study indicate that there is a positive and significant effect of peer teaching method assisted by e-module media on the understanding of concepts and scientific attitudes of seventh grade students on the material of Classification of Living Things. Based on the results of the Gain manova test from the pretest and posttest question sheets and the observation sheet obtained the Sig. (2-tailed) is 0.000 and 0.015 H0 is rejected and H3 is accepted